Effect of Soil Applied Silicon on Gas Exchange Parameters, Growth and Ion Content of Maize under Alkaline Stress - Natarajan, Gokula Priya; Sriramachandrasekharan, Malayappa Venkataraman; Manivannan, Rengarjan; Prakash, Muthu Arjuna Samy (International Journal of Bio-resource and Stress Management, 2021)
A pot experiment was conducted to understand the effect of soil applied silicon on maize crop growth under alkaline stress. The treatment consists of silicon levels (kg ha-1) – 0, 100 and150 and alkaline stress levels (mM) – 0, 25, 50, 75. The pots were arranged in completely randomized block design in factorial arrangement with three replications. The result revealed that the shoot and root length and chlorophyll content of maize were reduced with increasing alkaline stress. The percent reduction due to alkaline stress on shoot and root length was to tune of 3.6to 15.8 and 8.9 to 35.8, respectively and chlorophyll content 11.2 to 35.7. The sodium ion content increased, but potassium content and K Na-1 ratio decreased with alkaline stress. The gas exchange parameters viz., photosynthetic rate, stomatal conductance and transpiration rate were significantly decreased with alkalinity levels. The adverse effect of alkalinity on maize was turnround with intervention of soil applied silicon. The percent increase due to silicon intervention ranged from 4.3 to 12.6 in photosynthetic rate, 4.5 to 14.5 in stomatal conductance, 6.3 to 21.4 in transpiration rate, 7.0 to 20.9 and 8.4 to 29.3 in shoot and root potassium, 19.4 to 33.5 and 20.6 to 55.9 in shoot and root K Na-1. The percent decrease in sodium concentration in shoot and root ranged from 8.6 to 14.2 and 4.3 to 23.7. Between 100 and 150 kgs of silicon applied, the desired result was achieved with 150 kg Si ha-1. It is recommended to apply 150 kg Si ha-1 to maneuver the ill effects of alkalinity on maize.